Language issues of Brazilian pilots regarding structure: A comparative study between student pilots and SDEA test takers - Pacheco, Aline; de Moraes Garcia, Angela Carolina (The ESPecialist, 2020)
This article addresses the most common language problems of Brazilian pilots regarding structure, a fundamental skill in aeronautical communications (DOC 9835). We aim to present an overview of the most specific errors made by student-pilots and Santos Dumont English Assessment (SDEA) test takers and compare them in order to better understand their language competence. The qualitative analysis will be based on lists which feature data collected from classroom work (student pilots) and SDEA report forms (RFs). The study is intended to provide researchers with more tools to deal with Aviation English focusing on pilot performance, as well as to contribute to better curriculum design and improvements in assessment practices.